Methods for obtaining interocclusal records: a comparative review of analog and digital methods - Lau Nakamatsu, Valeria (2026)
Interocclusal record registration is a fundamental procedure in dental practice, both during the diagnostic phase and throughout prosthetic rehabilitation. However, conventional methods present significant challenges related to material handling, patient cooperation, and operator skill. Factors such as material dimensional instability, articulator manipulation, and model storage may compromise the accuracy of the final mounting. In this context, the incorporation of CAD/CAM technologies has made it possible to overcome several analog limitations and optimize the clinical workflow, although this technology continues to evolve. The aim of this article is to conduct a literature review on the accuracy of digital interocclusal records compared with analog ones, in order to provide updated evidence that may guide clinicians in selecting the most appropriate technique for occlusal analysis in each case.